Epidemiological and molecular characteristics of circulating CVA16, CVA6 strains and genotype distribution in hand, foot and mouth disease cases in 2017 to 2018 from Western India. Issue 6 (1st October 2020) - Gopalkrishna, Varanasi; Ganorkar, Nital
Abstract: Hand, Foot, and Mouth disease (HFMD) is a mild exanthematous and febrile disease occurs in children aged ≤10 years old. The present study highlights clinical, epidemiological characteristics, distribution of enterovirus (EV) types, and sub genotypes in HFMD cases reported during 2017 to 2018 in Western India. A total of 93 clinical samples collected from 68 HFMD cases were included. The presence of EV‐RNA was determined by 5'UTR based nested reverse transcription polymerase chain reaction followed by molecular typing, sub genotyping by VP1/2A junction or VP1, full VP1 gene amplification, and phylogenetic analysis. The study reports 80.64% (75/93) EV positivity and 94.66% (71/75) typing rate, with a predominant circulation of CVA16 and CVA6 strains. Sequence analysis revealed the presence of coxsackievirus (CV)A16 (57.7%), CVA6 (40.8%), and Echo1 (1.4%) strains. EV infections were predominantly observed in children aged 1 to 3 years old (43.9%). Although cases were reported throughout the year, peaked in July (15.8%) and August (24.6%) months and persisted till September (19.3%). All the CVA16 and CVA6 positive strains were genotyped using full VP1 gene amplification. All CVA16 Indian strains (n = 41) were clustered with rarely reported B1c sub genotype and CVA6 strains (n = 29) with E2 sub‐lineage. The study highlights the genetic characteristics of circulating CVA16, CVA6, and Echo1 strains in HFMD cases from Western India. The emergence of CVA16 B1c genotype and sub‐lineage E2 of CVA6 strains and their constant circulation further demands systemic surveillance studies on HFMD from different parts of India to facilitate the rapid diagnosis of CVA16 and CVA6 strains using the molecular and serological based approach and for intervention strategies. Highlights: Predominance of CVA16 and CVA6 strains in HFMD cases from western India. Circulation of CVA16 B1c sub genotype strains and CVA6 sub lineage E2 strains in HFMD cases, western India.